Two-body wear of occlusal splint materials against different antagonists - ÖZKAN, YASEMİN; ASLAN, YILMAZ UMUT (BMC, 2020)
Background This study aimed to demonstrate that the material of the occlusal splint can be chosen according to the needs of individual patients and contribute to the knowledge of the wear rate of these materials. Methods In this study, four occlusal splint materials (Sr Ivocap Heat Cured, Valplast, SR Ivocap Elastomer and Eclipse) and three antagonists (natural tooth enamel, inCoris TZI and IPS e.max Press ceramic materials) were used. Each wear test was performed using a chewing simulator (n = 16; test load: 50 N; number of cycles: 10,000, 20,000 and 30,000; continuous rinsing with water at 30 degrees C for the wet condition). The Shapiro Wilk test was used for normal distribution suitability. Antagonist on average wear quantities both main effects and interactions of material, cycle and condition factors were investigated by Univariate variance analysis. Multiple comparisons were examined using the Games-Howell test. Results There was a statistically significant effect of the difference in materials on the amount of wear (p < 0.001). Furthermore, there was a statistically significant difference among the mean values of all materials (p > 0.001). The highest mean value was obtained with Eclipse (0,318 mu m(3)), and the lowest mean value was obtained with Valplast (0,134 mu m(3)). Conclusion Our study found differences in the in vitro wear rate among various occlusal splint materials.
Keywords: Occlusal splints; Two-body wear; Splint materials; COMPOSITE; TEETH